Coupled Fixed Point Theorems in Topological Spaces with Size Function Topology - Gun Sunyeekhan (Abstract and Applied Analysis)
Regarding the concept of size function topology, this allows us to view the topological space X as a metric-like space. We prove the existence and uniqueness for a coupled fixed point of the map F:X×X⟶X satisfying some certain contractive conditions.